Splitting and jetting of cavitation bubbles in thin gaps. (10th August 2020) - Zeng, Qingyun; Gonzalez-Avila, Silvestre Roberto; Ohl, Claus-Dieter
Abstract : Abstract : We study the dynamics of cavitation bubbles and induced jets in a thin liquid gap bounded by two rigid walls. The bubbles are generated experimentally with a focused laser pulse and are compared to simulations. The gap height $H$ and the distance of the position of bubble nucleation $h$ with respect to the nearest wall are varied. The bubble dynamics is recorded at 500 000 frames per second and is compared to simulation results from the compressible volume of fluid solver based on OpenFOAM that takes into account viscosity and surface tension. Good agreement of the spatio-temporal bubble dynamics between experiments and simulations is obtained. The findings are that the parameter space consists of three regions with distinct jetting dynamics that are characterized by two dimensionless parameters: the normalized gap height, $\unicode[STIX]{x1D702}=H/R_{max}$, where $R_{max}$ is the spherical equivalent radius of the bubble at maximum expansion, and the normalized stand-off distance of the bubble measured from the centre of the gap, $\unicode[STIX]{x1D701}=(H/2-h)/R_{max}$ . The three qualitatively distinct jetting behaviours are the transferred jet impacting on the distant wall, the double jet as a result of a bubble splitting and impacting on both walls and the directed jet from a conically shaped bubble impacting on the closest wall. The impact velocity of the liquid jets onto the walls can reach more than $200~\text{m}~\text{s}^{-1}$ and strongly depends on the gap height and bubble position. The simulations reveal that the viscous boundary layers affect the bubble splitting and therefore the directions of jetting. Additionally, we found that with increasing length of the thin gap $L$ the bubble oscillation period increases and converges for sufficiently large gaps.